Short-term particulate matter contamination severely compromises insect antennal olfactory perception - Qike Wang; Genting Liu; Liping Yan; Wentian Xu; Douglas J. Hilton; Xianhui Liu; Wenya Pei; Xinyu Li; Jinbiao Wu; Haifeng Zhao; Dong Zhang; Mark A. Elgar (Nature Communications, 2023)
Abstract The consequences of sub-lethal levels of ambient air pollution are underestimated for insects, for example, the accumulation of particulate matter on sensory receptors located on their antennae may have detrimental effects to their function. Here we show that the density of particulate matter on the antennae of houseflies (Musca domestica) collected from an urban environment increases with the severity of air pollution. A combination of behavioural assays, electroantennograms and transcriptomic analysis provide consistent evidence that a brief exposure to particulate matter pollution compromises olfactory perception of reproductive and food odours in both male and female houseflies. Since particulate matter can be transported thousands of kilometres from its origin, these effects may represent an additional factor responsible for global declines in insect numbers, even in pristine and remote areas.